Hepatitis B virus mutation pattern rtL180M+A181C+M204V may contribute to entecavir resistance in clinical practice. Issue 1 (1st January 2019) - Liu, Yan; Zhou, Yi; Li, Xiaodong; Niu, Ming; Chen, Rongjuan; Shao, Jinman; Si, Lanlan; Luo, Dan; Lin, Yayun; Li, Le; Zhang, Kai; Xiao, Xiaohe; et al.
ABSTRACT: Background and Aims: Entecavir (ETV) resistance of hepatitis B virus (HBV) conventionally requires rt184, 202, or 250 mutations plus lamivudine-resistance mutation (rtM204V/I ± L180M). This study aimed to clarify whether rtL180M+A181C+M204V mutations may contribute to HBV ETV resistance. Methods: Serum samples were collected from 22, 009 patients who underwent resistance testing in Beijing 302 Hospital from 2007 to 2016. HBV reverse transcriptase (RT) gene was screened by direct sequencing and verified by clonal sequencing. Phenotypic analysis was performed for evaluating replication capacity and drug susceptibility. Results: Classical ETV-resistance mutations of HBV were detected in 1252 patients who were receiving ETV therapy. The rtA181C mutation was detected with rtL180M+M204V mutations in 18 lamivudine-experienced ETV-treated patients, and the emergence of the mutations was associated with virological breakthrough or inadequate virological response to ETV. Patient-derived representative rtA181C-containing mutants, rtL180M+A181C+M204V, rtL180M+A181C+M204V+M250V, and rtL180M+A181C+S202G+M204V, exhibited 45.7%, 25.9%, and 25.0% replication capacity and 85.6-, 356.1-, and 307.1-fold decreased susceptibility to ETV respectively compared to the wild-type strain, while the three mutants remained sensitive to tenofovir (TDF). Artificial elimination of rtA181C largely restored the rtL180M+A181C+M204V mutant's sensitivity to ETV. Molecular modelling of viral RT binding to ETV showed that the rtL180M+A181C+M204V mutant had a less stable conformation compared to rtL180M+M204V mutant. In clinical practice, undetectable serum HBV DNA was achieved in two of five longitudinally followed rtA181C-positive patients who received switching-to TDF therapy, but not in the other three who received add-on adefovir therapy during observation. Conclusions: Both clinical and experimental data support rtL180M+A181C+M204V as a novel non-classical ETV-resistance mutation pattern.